A cationic fluorescent probe for highly selective detection of sodium dodecyl sulfate (SDS) by electrostatic and hydrophobic self-assembly. Issue 29 (6th July 2021) - Chen, Hongrui; Mu, Xinyue; Li, Jian; Qin, Yuqi; Yan, Liqiang
Abstract : A cationic fluorescent probe for highly selective detection of SDS by electrostatic and hydrophobic self-assembly. Abstract : Sodium dodecyl sulfate (SDS) has a wide range of applications in the chemical industry due to its excellent characteristics including good emulsification, foaming, water solubility and stability, easy synthesis and low price. However, it is a kind of anionic surfactant which is slightly toxic to the human body, and use of a large amount will cause potential pollution of the environment. Therefore, the development of a simple method to realize the monitoring of SDS in the environment is of great significance. Herein, a cationic fluorescent probe was prepared by the condensation reaction between 4-di- p -tolylamino-benzaldehyde and 3-ethylbenzothiazolium iodide. It can be used for the quantitative determination of SDS in the range of 5–50 μM showing red fluorescence and high selectivity by forming banded assemblies. This work provides an effective tool based on a new strategy for the detection of SDS.